Features of coping strategies of older adolescents from single-parent families - Ivanova O.I.; Busarova O.R. (Психология и право, 2020)
The article presents the results of an empirical study with the purpose to determine the characteristics of the coping strategies of older adolescents from single-parent families. The sample consisted of 98 students of a Moscow secondary school at age of 14-16, 60 of which were adolescents from full families (30 boys and 30 girls) and 38 - from single-parent families (15 boys and 23 girls). The study was conducted using the questionnaires “Strategic Approach to Coping Scale, SACS” (S. Hobfall) and “Parents are Assessed by Children” - a modification of the test “Analysis of Family Relationships” by E.G. Eidemiller and V.V. Yustitskis . The paper identifies the dominant coping strategies of older adolescents and assesses their constructiveness, establishes significant differences in the coping strategies of adolescents from full families and single-parent ones, identifies family education styles that are predictors of a number of coping strategies of older adolescents, including those specific to boys and girls brought up in both types of families. The results of the study will help determine the direction of work on the correction negative coping strategies in adolescents from a single-parent family.